ANALISA TINGKAT PENCEMARAN AIR BAWAH TANAH DENGAN METODE GEOLISTRIK KONFIGURASI SCHLUMBERGER DI KECAMATAN TAMPAN KOTA PEKANBARU - Juandi M; Usman Malik; Melki Leonardo (Komunikasi Fisika Indonesia, 2018)
The research analyzing ground water contamination based on Geo-electrical methods near 2 point, that is in Cipta Karya street (without waste pile) and Srikandi street (with waste pile), Kecamatan Tampan Riau. Data was processed using Software Progress, with the results of processing in the form of depth, thickness and number of layers and the resistivity value. Has been done the results obtained showed that the resistivity value on Cipta Karya road without garbage pile was 57.10-4955.00 Ohm.m at depth 0,00-346,00 Meter and on Srikandi street with garbage pile was 68.90-4008.00 Ohm.m at depth 0,00-367,00 Meter. Geo-electrical data measurements in Cipta Karya and Srikandi there are 5 layers of soil, that is cover layer, clay loam layer, alluvium layer, sand layer and bedrock layer. Based on the above resistivity values and depth, all points considered un polluted by leachet because the resistivity value is far above 10 Ohm.m (fresh water). Resistivity values indicate that the leachet does not seep into the soil and spread to swamps which are right next to the garbage pile(Srikandi road).